The Development of online-based Management Information System Application for Individual (Chungking-Reframing) at the Chungking Framing Social Institution - Warsono, Tri; Akbar, Ma’ruf; Tunas, Billy (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to develop an online-based management information system application for individual counseling techniques at the Chungking Framing Social Institution. The research question in this study is how to develop online information-based symptom applications for individual counseling techniques. The method used in this study is a mixed method with a quantitative approach. In this study, it employs the waterfall development model, where each stage is always evaluated so that results are obtained according to the needs. To collect the data, the Likert scale of the questionnaire as an instrument is used. In the pilot study, it involved 26 respondents, and it was found that online-based applications greatly made it easier to consult on personal matters. This research found that the application of an online-based management information system for counseling techniques is very helpful, efficient, and effective in consulting personal problems. The development of science and technology is so rapid and the development of information and communication systems that increasingly lead to changes and progress in various aspects of life. Online-based information system applications for counseling are very helpful for closed individuals in expressing their problems openly.